3x-2(x-4)=8-2x+15

Simple and best practice solution for 3x-2(x-4)=8-2x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-2(x-4)=8-2x+15 equation:


Simplifying
3x + -2(x + -4) = 8 + -2x + 15

Reorder the terms:
3x + -2(-4 + x) = 8 + -2x + 15
3x + (-4 * -2 + x * -2) = 8 + -2x + 15
3x + (8 + -2x) = 8 + -2x + 15

Reorder the terms:
8 + 3x + -2x = 8 + -2x + 15

Combine like terms: 3x + -2x = 1x
8 + 1x = 8 + -2x + 15

Reorder the terms:
8 + 1x = 8 + 15 + -2x

Combine like terms: 8 + 15 = 23
8 + 1x = 23 + -2x

Solving
8 + 1x = 23 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
8 + 1x + 2x = 23 + -2x + 2x

Combine like terms: 1x + 2x = 3x
8 + 3x = 23 + -2x + 2x

Combine like terms: -2x + 2x = 0
8 + 3x = 23 + 0
8 + 3x = 23

Add '-8' to each side of the equation.
8 + -8 + 3x = 23 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 23 + -8
3x = 23 + -8

Combine like terms: 23 + -8 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| -3-4x=5x+24 | | 5-(1/2)x=(1/8)x | | 5x^2-4x+3=6 | | 11c=9c+14 | | 2-2x-5/5=x+9/4 | | 12x-3x-7=11 | | 56-s=45-9 | | 1+(3*7)=z | | 1+(3*7)= | | 1/2-1=1/44 | | -24p^2q^2+(-2pq)+3= | | 2x-6x+21=-13 | | -4x+21=-13 | | 28x+4+7x+7=102 | | 1xy=78 | | 1*y=787 | | 1y=78 | | xy=-40 | | ax+5x-4=10 | | 4-4x^2+4xy-y^2= | | 15-1/2x=1/4x | | x/5-x/3=8/15 | | 5/8+(-7/12) | | -4/7+2/7 | | 4x-7y=29 | | 5/21x=2/3x-1/7 | | 2(3x-1)=5(2-7x) | | 3-x=2x+18 | | 2x+15=0 | | x+(0.2746x)=866.73 | | x+(0.2746x)=1000 | | 2abc+3a+4b= |

Equations solver categories